Comparative Study of Densitometry and Videodensitometry for Quantitating the Active Pharmaceutical Ingredients Using Thin Layer Chromatography – Systematic Review - Firmansyah Ardian Ramadhani; Idha Kusumawati; Riesta Primaharinastiti; Subhan Rullyansyah; Fajar Jamaluddin Sandhori; Hanif Rifqi Prasetyawan (Universitas Airlangga, 2023)
Background: Chromatography is one of the analytical techniques widely used for the quality control process in the pharmaceutical industry. One of the analytical methods used in drug analysis is Thin Layer Chromatography (TLC). The analysis process of TLC can be performed using densitometry (scanner) or videodensitometry (videoscan). The principal analysis of densitometry (scanner) is based on the density measured from each spot on the TLC plate using a specific wavelength range, and videodensitometry (videoscan) is performed by taking pictures of the plate using a Visualizer at a specific wavelength. Objective: This review article discusses the application of densitometry and videodensitometry methods for quantitative analysis of pharmaceutical products. Methods: This study was conducted using a systematic review method using the PRISMA statement from January to April 2023. Four databases were searched: PubMed, ScienceDirect, Scopus, and Google Scholar with inclusion criteria: studies on thin layer chromatography analysis using densitometry and videodensitometry. Results: Based on the ten articles in this study, it is known that the active ingredient concentrations in pharmaceutical products can be determined using densitometry and videodensitometry. The statistical analysis results show no significant difference between the two methods' chemical concentrations of active ingredients in pharmaceutical products. Conclusion: TLC densitometry and videodensitometry is a valid methods analysis that can be used for quantitating the active pharmaceutical ingredient concentration in finished pharmaceutical products.